Bit-wise cryptanalysis on AND-RX permutation Friet-PC. (June 2021) - Ito, Ryoma; Shiba, Rentaro; Sakamoto, Kosei; Liu, Fukang; Isobe, Takanori
Abstract: This paper presents three attack vectors of bit-wise cryptanalysis including rotational, bit-wise differential, and zero-sum distinguishing attacks on the AND-RX permutation Friet-PC, which is implemented in a lightweight authenticated encryption scheme Friet . First, we propose a generic procedure for a rotational attack on AND-RX cipher with round constants. By applying the proposed attack to Friet-PC, we can construct an 8-round rotational distinguisher with a time complexity of 2 102 . Next, we explore single- and dual-bit differential biases, which are inspired by the existing study on Salsa and ChaCha, and observe the best bit-wise differential bias with 2 − 9 . 552 . This bias allows us to practically construct a 9-round bit-wise differential distinguisher with a time complexity of 2 20 . 044 . Finally, we construct 13-, 15-, and 17-round zero-sum distinguishers with time complexities of 2 31, 2 63, and 2 127, respectively. To summarize our study, we apply three attack vectors of bit-wise cryptanalysis to Friet-PC and show their superiority as effective attacks on AND-RX ciphers.